Two dimensional quantum and reliability modelling for lightly doped nanoscale devices - ElKashlan, Rana (AUC Knowledge Fountain, 2018)
The downscaling of MOSFET devices leads to well-studied short channel effects and more complex quantum mechanical effects. Both quantum and short channel effects not only alter the performance but they also affect the reliability. This continued scaling of the MOS device gate length puts a demand on the reduction of the gate oxide thickness and the substrate doping density. Quantum mechanical effects give rise to the quantization of energy in the conduction band, which consequently creates a larger effective bandgap and brings a displacement of the inversion layer charge out of the Si/SiO2 interface. Such a displacement of charge is equivalent to an increase in the effective oxide layer thickness, a growth in the threshold voltage, and a decrease in the current level. Therefore, using the classical analysis approach without including the quantum effects may lead to perceptible errors in the prognosis of the performance of modern deep submicron devices. In this work, compact Verilog-A compatible 2D models including quantum short channel effects and confinement for the potential, threshold voltage, and the carrier charge sheet density for symmetrical lightly doped double-gate MOSFETs are developed. The proposed models are not only applicable to ultra-scaled devices but they have also been derived from analytical 2D Poisson and 1D Schrodinger equations including 2D electrostatics, in order to incorporate quantum mechanical effects. Electron and hole quasi-Fermi potential effects were considered. The models were further enhanced to include negative bias temperature instability (NBTI) in order to assess the reliability of the device. NBTI effects incorporated into the models constitute interface state generation and hole-trapping. The models are continuous and have been verified by comparison with COMSOL and BALMOS numerical simulations for channel lengths down to 7nm; very good agreement within Â±5% has been observed for silicon thicknesses ranging from 3nm to 20nm at 1 GHz operation after 10 years.